ECONOMIC FACTORS OF THE ENEOLITHIC PERIOD IN THE SOUTHERN ARAL REGION AND THE LOWER ZARAFSHAN VALLEY - Sultanov Samandar Mahmud o‘g‘li (Bright Mind Publishing, 2025)
This article highlights the socio-economic development factors of Eneolithic society in the Southern Aral region and the Lower Zarafshan Valley.
Keywords: Vinogradov A.V., Itina M.A., Kes A.S., Mamedov E.D., Baratov P., Mamatqulov M., Rafikov A., Kabirov J., Sagdullaev A., Ibragimov R.Z., Tolstov S.P., Itina M.A., G‘ulomov Ya.G‘., Islomov U.I., Asqarov A., Xolmatov N.U., Khorezm, Lower Zarafshan, Kyzylkum, Kamyshli, Darbazakir